2015
DOI: 10.1038/srep13683
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the residual inactivation of Microcystis aeruginosa by dielectric barrier discharge

Abstract: We report the new insight into the dielectric barrier discharge (DBD) induced inactivation of Microcystis aeruginosa, the dominant algae which caused harmful cyanobacterial blooms in many developing countries. In contrast with the previous work, we employed flow cytometry to examine the algal cells, so that we could assess the dead and living cells with more accuracy, and distinguish an intermediate state of algal cells which were verified as apoptotic. Our results showed that the numbers of both dead and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Zhang et al (2017) compared the effectiveness of four different processes against S. aureus using a DBD plasma source, and 3 log reduction was obtained in an indirect treatment, while the inactivation rate for a direct treatment was 7 log under the same conditions. Pemen et al (2017) observed 0.8 log reduction of Staphylococcus epidermidis with indirect plasma treatment at 90 W after 20 min, whereas 2.4 log reduction was achieved after 3 min direct plasma treatment at lower power of 60 W. The higher inactivation rates obtained with direct treatment were reported to result from the fact that short-living reactive species, such as atomic oxygen or hydroxyl radicals can cause initial damage during the direct discharge period, and the inactivation efficiency can be further enhanced by the long-living reactive species generated in water (Li et al, 2015;Zhang et al, 2017). Another factor correlated with PAW antimicrobial efficiency is the generation mode, that is, whether the plasma plume is above or beneath the water surface.…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al (2017) compared the effectiveness of four different processes against S. aureus using a DBD plasma source, and 3 log reduction was obtained in an indirect treatment, while the inactivation rate for a direct treatment was 7 log under the same conditions. Pemen et al (2017) observed 0.8 log reduction of Staphylococcus epidermidis with indirect plasma treatment at 90 W after 20 min, whereas 2.4 log reduction was achieved after 3 min direct plasma treatment at lower power of 60 W. The higher inactivation rates obtained with direct treatment were reported to result from the fact that short-living reactive species, such as atomic oxygen or hydroxyl radicals can cause initial damage during the direct discharge period, and the inactivation efficiency can be further enhanced by the long-living reactive species generated in water (Li et al, 2015;Zhang et al, 2017). Another factor correlated with PAW antimicrobial efficiency is the generation mode, that is, whether the plasma plume is above or beneath the water surface.…”
Section: 1mentioning
confidence: 99%
“…Moreover, the SEM images of S. aureus after PAW treatment showed that the level of morphology damage depended on the working gas as well, which was in accordance with the inactivation efficacy. Though it is difficult to conclude which working gas works the best for inactivation effect of PAW, there seems to be an agreement that the addition of a small amount of oxygen to noble gas can improve the antimicrobial efficacy of PAW (Ikawa, Kitano, & Hamaguchi, 2010; Smet et al., 2019), and the usage of air as working gas usually leads to greater inactivation efficacy than noble gases (Li, Zhang, & Huang, 2015), which were the same cases for direct plasma treatment (Galvin et al., 2013; Lee et al., 2012; Surowsky, Fröhling, Gottschalk, SchlĂŒter, & Knorr, 2014). The phenomenon may be mainly due to the higher concentration of ROS formed in plasma in the presence of oxygen, including hydroxyl radicals, singlet oxygen, atomic oxygen, ozone, which have been regarded to make dominating contribution to the antimicrobial property of PAW (Rowan et al., 2007; Vlad & Anghel, 2017; Zhang et al., 2012).…”
Section: Factors Influencing the Inactivation Efficiency Of Pawmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcystins are toxins produced by cyanobacteria, and can cause detrimental effects on farm animal health (53). Moreover, DBD-generate -NTP has been shown to inactivate residues of cyanobacteria which cause algal bloom in water (54). Another study has reported that pulsed plasma gas discharge destroys waterborn enteroparasites which infect both farm animals and humans.…”
Section: Ntp Increases the Microbiological Physical And Chemical Quamentioning
confidence: 99%
“…We observed the specific apoptotic physiological hallmarks, such as phosphatidylserine exposure on the cell membrane and increased expression of proteins with caspase-like substrate specificity [116]. Moreover, another study has shown the NTP- induced PCD in microorganisms [149]. Li et al explained the Microcystis aeruginosa inactivation by intracellular accumulation of plasma- produced ROS leading to apoptosis [149].…”
Section: Non-thermal Plasma As a Tool For Non-specific Bacterial Kmentioning
confidence: 99%